Sodium salicylate during the first 7 days of lactation affects the entire lactation - Jaymelynn K. Farney; Laman Mamedova; J. Ernest Minton; J. F. Coetzee (Kansas Agricultural Experiment Station Research Reports, 2012)
Inflammation has been proposed as a contributor to metabolic disorders in transition dairy cows. The purpose of this experiment was to determine if a non-steroidal anti-inflammatory drug, sodium salicylate (SS), benefits transition cows. At calving, 78 cows [primiparous (1P) n = 39; 2nd lactation (2P) n = 24; ≥3 lactations (3P) n = 15] were assigned alternately to either a control or SS treatment for 7 days and production responses were evaluated through the entire lactation. Treatment was administered via individual water bowls, delivering a mean of 123 ± 5.5 (mean ± standard deviation) grams salicylate per day during the 7 days of treatment. Cows were followed throughout the lactation by monthly milk yield and component testing, and the effects of treatment on the risk of leaving the herd and on normalized 305-day milk, fat, and protein yields were determined by Fisher's exact test and mixed model analysis, respectively. Treatment influenced both 305-day milk and fat yields differently across parities. Milk yield was increased by 17% in 3P SS cows (4,374 ± 1,549 lb greater for 3P SS cows). Primiparous SS cows tended to produce 2,155 ± 824 lb less 305-day milk than control cows; no differences were detected for 2P cows. Furthermore, 3P SS cows produced 285 ± 50 lb more 305-day milk fat and tended to produce 108 ± 40 lb more 305-day milk protein. No effects were detected in 1P or 2P cows. A treatment by parity interaction was observed for the risk of leaving the herd where 1P cows treated with SS tended to have a greater risk of leaving the herd than controls (30% vs. 6% risk). Treatment did not alter herd retention in 2P or 3P groups, and SS had no effect on the risk of leaving the herd overall. Results indicate that SS has long-term effects on lactation characteristics of aged cows, particularly on fat metabolism, but has potential negative effects for primiparous cows.; Dairy Day, 2012, Kansas State University, Manhattan, KS, 2012; Dairy Research, 2012 is known as Dairy Day, 2012
Keywords: Dairy Day; 2012; Kansas Agricultural Experiment Station contribution; no. 13-030-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1075; Dairy cows; Lactation; Postpartum health; Sodium salicylate